2014
DOI: 10.7314/apjcp.2014.15.8.3575
|View full text |Cite
|
Sign up to set email alerts
|

Staurosporine Induced Apoptosis Rapidly Downregulates TDP-43 in Glioma Cells

Abstract: TDP-43 is a ubiquitously expressed DNA/RNA binding protein that has recently attracted attention for its involvement in neurodegenerative diseases. While TDP-43 has been found to participate in various important cellular activities including stress and apoptosis, little is known about its role in cancer cells. Here we report that staurosporine (STS) induced apoptosis in U87 glioma cells is associated with rapid downregulation of TDP-43 at both mRNA and protein levels. The latter is dependent on activation of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Although caspase 3/7 is not essential for methuotic cell death [8, 22], we found that caspase 3/7 activation as well as endogenous caspase 3/7 activity is counter regulated by exogenous ATP (Figure 2). In the glioma cell line #12537-GB, Vac-induced caspase 3/7 activation and STS-induced apoptosis occur within a similar time frame (Figures 2, 3, [32, 33]). However, the number of PI-positive nuclei in STS- and Vac-treated glioma cells differed between Vac- and STS-induced cell death (Figure 3A).…”
Section: Discussionmentioning
confidence: 87%
“…Although caspase 3/7 is not essential for methuotic cell death [8, 22], we found that caspase 3/7 activation as well as endogenous caspase 3/7 activity is counter regulated by exogenous ATP (Figure 2). In the glioma cell line #12537-GB, Vac-induced caspase 3/7 activation and STS-induced apoptosis occur within a similar time frame (Figures 2, 3, [32, 33]). However, the number of PI-positive nuclei in STS- and Vac-treated glioma cells differed between Vac- and STS-induced cell death (Figure 3A).…”
Section: Discussionmentioning
confidence: 87%
“…These results imply that TDP43 could be a drug target in breast cancer, especially in TNBC. Interestingly, it has been reported that many antitumor drugs can alter TDP43 expression in cancer cells ( 44 46 ), further suggesting that TDP43 might provide a molecular basis for the treatment of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of TDP-43 by a specific siRNA dramatically enhances the cytotoxicity of STS, suggesting that normal levels of TDP-43 are protective for cancer cells under apoptotic insult (Nan et al 2014). This observation is consistent with previous analysis showing TDP-43 as survival factor under oxidative stress conditions (Higashi et al 2013).…”
Section: Tdp-43mentioning
confidence: 99%